Internal Marketing, Internal Service Quality, Empowerment, And Business Performance: An Empirical Study Of Private Higher Education Institutions In Malaysia - Ng , Peng Long (2010)
This study aims to examine an IM theoretical framework in the Malaysian private higher education industry. The moderating effect of empowerment between the relationship of IM practices and perceived internal service quality is being examined. Survey research using self-administered questionnaires is carried out on 325 private higher education institutions located in Penang, Klang Valley and Johor. The results of this study indicate that IM practices comprise of four components, namely departmental coordination and training, proactive HR approach, leadership capability, and internal communication.